Exploring how healthcare teams balance the neurodynamics of autonomous and collaborative behaviors: a proof of concept - Stevens, Ronald; Galloway, Trysha L. (Frontiers in Human Neuroscience, 2022)
Team members co-regulate their activities and move together at the collective level of behavior while coordinating their actions toward shared goals. In parallel with team processes, team members need to resolve uncertainties arising from the changing task and environment. In this exploratory study we have measured the differential neurodynamics of seven two-person healthcare teams across time and brain regions during autonomous (task work) and collaborative (teamwork) segments of simulation training. The questions posed were: 1) whether these abstract and mostly integrated constructs could be separated neurodynamically; and, 2) what could be learned about task work and teamwork by trying to do so? The task work and teamwork frameworks used were Neurodynamic Information (NI), an electroencephalography (EEG) derived measure shown to be a neurodynamic proxy for the pauses and hesitations associated with individual uncertainty, and inter-brain EEG coherence (IBC) which is a required component of social interactions. Both scalp-averaged and second by second dynamic analyses of the NI and IBC data streams showed that the collaborative neurodynamics differed in magnitude, duration, scalp locations, and simulation segments where expressed, from when the same team members were resolving uncertainty. These studies show that proxies for fundamental properties of teamwork and taskwork can be separated neurodynamically during team performances of ecologically valid tasks. The persistent expression of NI and IBC were not simultaneous suggesting that it may be difficult for team members to maintain inter-brain coherence while simultaneously reducing their individual uncertainties. Lastly, these separate dynamics occur over time frames of 15-30s providing time for real-time detection and mitigation of individual and collaborative complications during training or live patient encounters.